Physicians as viral hepatitis advocates: empowerment through education - Rastogi, Aayushi; Syed, Sabin; Gupta, Ekta; Bansal, Akanksha; Varshney, Mohit; Keshan, Pranav (International Journal of Advances in Medicine, 2021)
Background: Viral hepatitis is the most serious infections due to its asymptomatic nature for a long period and complications like liver cirrhosis and hepato cellular carcinoma. Also, available literatures suggest low vaccination status, poor to moderate knowledge about prevention and management of viral hepatitis. Moving forward, physicians can act as advocates in disseminating the correct knowledge about prevention and transmission of viral hepatitis. With this background one-day training program for physicians was conceptualised under project PRAKASH to educate and empower them about prevention and management of viral hepatitis. Methods: A pre-post study design was undertaken among the physicians who registered themselves for hepatitis induction program. An online link to the knowledge, attitude and practice (KAP) questionnaire consisted of 59 questions of knowledge (35 questions), attitude (12 questions) and practice (12 questions) along with demographic variables was shared with the registered participants. Same knowledge questions were asked during post-test. Paired-t-test and Independent samples t-test were used in analysis using statistical package for the social sciences (SPSS) v-21. Level of significance was taken at p<0.05. Results: A total of 204 clinicians were trained over five training and pre-post was available for 170 participants. The mean knowledge, attitude and practice scores were found to be 25.11±4.85, 50.17±6.86, 20.18±3.90 out of total score of 35, 60 and 24 respectively. Post knowledge score had increased significantly when compared with pre-score. Pre-knowledge score was found significant with experience level. Conclusions: Overall, study observed significant improvement of knowledge among physicians which can be attributable to training program and this program can be up scaled and help in empowering the physicians on various health-related topics across the country.